THE EFFECT OF PARATRANSIT, VEHICLES ON CAR SPEEDS IN BANDUNG - Darma Setiawan, buddy
This study in Bandung, Indonesia, attempted to assess the effect on car speeds of stops by motorized four-wheeled paratransit vehicles. There are no designated stopping places for them, and these vehicles stop at any point on the road to pick up and set down passengers. The effects of long stops, when the vehicles waited for passengers to appear, were not measured. The study was carried out on five roads of varying width. The following conclusions were reached: (1) At each site there was an approximately linear relationship between flow and speed of cars, both with and without stops by paratransit; (2) Except on the widest road, the speed of cars when paratransit vehicles were stopping was less than when they were not, and this effect increased with increasing flow; (3) At very low flows, car speeds increased with road width, with and without stops by paratransit vehicles; (4) Car speeds were found to be correlated with 'the number of stops by paratransit vehicles rather better than with their aggregate stopped time; (5) The effect of each stop by paratransit on car speed was greatest on the 7 metre wide road, getting less on narrower and wider roads; (6) An extra stop by paratransit delayed cars by about 1.7 seconds on road widths of 5 - 7 metres,. reducing to zero at 11 metres .